PRA-RANCANGAN INDUSTRI OLAHAN VANILI (VANILLA PLANIFOLIA ANDREWS) DENGAN SISTEM PENGERINGAN LAMPU PIJAR: PENGERINGAN VANILI (VANILLA PLANIFOLIA ANDREWS) MENGGUNAKAN PANAS RADIASI INFRAMERAH DAN SIRKULASI UDARA - Rahayu, Puji
Vanilla is an earthy herb that has high economic value. This is due to the flavour content contained in vanilla and the handling process which takes a long time. This flavour content will be formed during the curing process. One of the curing processes that are very important in improving the quality of vanilla is the drying process. Currently, most Indonesian farmers carry out the drying process using sunlight. This study aims to evaluate the drying process of vanilla using a simple dryer using infrared lamps and air circulation. In addition, mathematical modelling that describes the drying characteristics is also determined. The 9 months vanilla which has been through the withering and curing process is dried using an infrared dryer. Experiments were carried out with a one-variable-at-a-time (OVAT) design with two test variables, namely fan voltage (4V, 6V, and 8V) and drying capacity (1 tray, 2 trays, and 3 trays) carried out in triplo. The results of the evaluation of the drying process are seen based on the evaluation of the system and the drying results. The evaluation of the drying system includes the specific energy consumption (SEC) value, activation energy, and energy efficiency, while the evaluation of the drying results includes physical and chemical characteristics. The results showed that the increase in fan voltage did not have a significant effect on drying vanilla. Furthermore, the drying capacity has an influence on the efficiency of the dryer and the specific energy consumption (SEC) where large capacity will increase efficiency and decrease the SEC value. The mathematical model that describes the drying characteristics of vanilla is Wang-Singh. When viewed from the evaluation of the results of drying, it is found that vanilla that is dried with an effective voltage and capacity for 6 days can reduce the moisture content to 37.248% and produce a vanillin content value of 3.12% and an ash content of 2.25%.